Successful treatment of primary Sjögren’s syndrome complicated with primary biliary cirrhosis and lung involvement - Akif Altınbaş; Güneş ARIK; Umut KALYONCU; Ali AKDOĞAN; Ömer KARADAĞ; Bünyamin KISACIK; A. İhsan ERTENLİ (Turkish Journal of Gastroenterology, 2019)
-